P14 Mycophenolate mofetil in patients with autoimmune hepatitis intolerant to azathioprine. (16th November 2010) - Jothimani, D; Jothimani, D; Warshow, U; Barnardo, A; Cramp, M; Mitchell, J; Cross, T
Abstract : Introduction: Autoimmune hepatitis (AIH) is an immune mediated necroinflammatory condition of the liver. The majority of patients respond to the standard treatment combination of prednisolone and azathioprine. Twenty percent of patients either don't respond, or are intolerant to azathioprine. Several case series supports the use of mycophenolate mofetil (MMF) as a second line agent in refractory AIH. Its role is unclear in patients intolerant to azathioprine. Aim: To evaluate the efficacy and tolerability of MMF for the management of AIH. Method: A retrospective case note review from January 2000 to March 2010 in patients diagnosed with AIH (immune profile and liver biopsy). Patients on MMF were identified and evaluated. Treatment response to MMF was defined as a biochemical remission within 4 weeks of treatment commencement and treatment failure as either a non-response or relapse while on standard therapy. Results: 117 patients with autoimmune hepatitis were identified. 20/117 (17%) received MMF. The median age was 56 years (18–79 years) with male/female, 1:7. Three patients had overlap syndrome with autoimmune cholangitis, PSC and PBC, and six had cirrhosis. All patients were commenced on prednisolone for induction at a median dose of 30 mg (7.5–40 mg) and azathioprine within 3 months for remission. Azathioprine was discontinued due to intolerance following its adverse events, such as leucopenia, nausea and diarrhoea in 18 patients within 4 months (0–24 months). Two patients were true non-responders to azathioprine. All these patients were commenced on MMF at a median dose of 1 g twice daily in addition to low dose maintenance prednisolone. At a median follow-up of 47 months (5–83 months), MMF was well tolerated and 14/19 patients (one lost to follow-up) remained in remission including five patients with cirrhosis. Intolerance to MMF was seen in three patients (skin rash, hair loss) and poor response in two patients. Conclusion: Our case series supports the use of MMF as a second-line agent in AIH patients intolerant to azathioprine. It was well tolerated in patients including those with cirrhosis.